Descriptionstressor and Coping Mechanisms in Adolescents - Pany, Olivia Carla Yeany Dae; Tololiu, Tinneke A.; Kanine, Esrom (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2022)
Background: In adolescence, a person is expected to be able to form a style or color in his life, one of which is by becoming an independent teenager and not being a shadow of stress. Stress is a reality of everyday life, stress is any change that requires adjustment. Objective: To find out stressors and coping mechanisms in adolescents based on the results of research articles. Method: This research uses a literature review type of research, namely using the results of previous research through research journals. To obtain data that is appropriate to the topic, researchers conducted a search for national and international journals in two databases, namely Google Scholar, Pubmend, using keywords with boolean operators (AND, OR, and NOT). The keywords used, stress, coping, and adolescents are listed in each journal title obtained. With the condition that the journals searched were from 2017-2020 and the researcher found 8 journals that were used for the literature review. Results and analysis: Researchers found 8 articles that were appropriate and met the inclusion criteria regarding the topics discussed, namely descriptions of stressors and coping mechanisms in adolescents, two of which were taken in international journals, two of which discussed dysmenorrhea stressors and the others discussed educational stressors and some Most use adaptive coping mechanisms in solving problems. Conclusion: Based on the literature review, the researcher concluded that there is a description of stressors and coping mechanisms in adolescents. Adolescents react to stress in different ways and most use adaptive coping mechanisms in dealing with stressors, there are also a small number who use maladaptive coping mechanisms. Key words: stress, coping, teenagers.